2015
DOI: 10.1136/bmjopen-2015-008563
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and prognostication of neurological deterioration in patients with acute ICH: a hospital-based cohort study

Abstract: ObjectivePatients with intracerebral haemorrhage (ICH) are at high risk of neurological deterioration (ND). We aimed at establishing predictors of early ND (END) as well as late ND (LND) and at exploring the impact of neurological stability during the first week on long-term prognosis.DesignWe conducted this study as a retrospective cohort study. ND was evaluated based on the consciousness and severity of neurological symptoms. ND during the first 24 h after admission was defined as early ND and from 24 h to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
2
24
0
2
Order By: Relevance
“…But we note that the PPV was reported in one of these studies 18 , and it consistent with our current findings. There have also been additional spot sign publications since our initial search strategy 39 . This was unavoidable due to the prolonged timelines required to acquire regulatory approvals necessary for access to patient-level data, particularly across national jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
“…But we note that the PPV was reported in one of these studies 18 , and it consistent with our current findings. There have also been additional spot sign publications since our initial search strategy 39 . This was unavoidable due to the prolonged timelines required to acquire regulatory approvals necessary for access to patient-level data, particularly across national jurisdictions.…”
Section: Discussionmentioning
confidence: 99%
“…As only 4 studies focussed upon ICH in isolation, there is limited data about ICH-END incidence in relation to biomarkers, but amongst the 3 using a higher threshold, 12.2% deteriorated, comparable to ischaemic stroke. In cohort studies, END rates up to 30% have been reported following ICH [58], but differences are likely to reflect whether the clinical setting is a stroke unit without pre-selection or a specialist neurosurgical unit. Overall, incidence of END fell with advancing study publication year, independently of neurological threshold and time window.…”
Section: Discussionmentioning
confidence: 99%
“…These should include reports of standardised clinical and radiological data, such as the Alberta Stroke Program Early CT Score [66] for ischaemic stroke and haematoma volume for ICH [58]. Other novel biomarkers with a promising pathophysiological basis were considered by single studies, but have not been further developed.…”
Section: Recommendationsmentioning
confidence: 99%
“…[ 21 ] A retrospective cohort study in ICH patients suggested that relatively easy and effective risk stratification of early neurological deterioration is possible at admission based on the presence of a “spot sign” (suggestive of active hemorrhage) on the initial brain CTA imaging or extensive degree of intraventricular hemorrhage, whereas risk stratification of late neurological deterioration is possible based on specific clinical parameters assessed at admission such as degree of comorbidity (Charlson index), stroke severity, and/or degree of intraventricular hemorrhage. [ 22 ]…”
Section: Diagnosis and Management Of The Stroke Patients In Neurointementioning
confidence: 99%